Privatizing welfare in the Middle East : kin mutual aid associations in Jordan and Lebanon. - Baylouny, Anne Marie (Indiana series in Middle East studies., 2010)
Anne Marie Baylouny examines previously undocumented effects of neoliberal economic reforms on middle classes in the Middle East. As the state's safety network has been withdrawn, kin-based mutual aid associations—organized around new definitions of kinship and identity and geared to contemporary market and labor needs—have taken its place. Such organizations provide a measure of social and economic security for their members, and have come to dominate civil society in Jordan and Lebanon. Based on extensive fieldwork and interviews with members, non-members, and policy makers, Privatizing Welfare in the Middle East provides compelling new insights into democratization, liberalization, and civil society -- Présentation de l'éditeur.